Allergen immunotherapy and/or biologicals for IgE‐mediated food allergy: A systematic review and meta‐analysis. Issue 6 (19th January 2022) - de Silva, Debra; Rodríguez del Río, Pablo; de Jong, Nicolette W.; Khaleva, Ekaterina; Singh, Chris; Nowak‐Wegrzyn, Anna; Muraro, Antonella; Begin, Philippe; Pajno, Giovanni; Fiocchi, Alessandro; Sanchez, Angel; Jones, Carla; et al.
Abstract: Background: There is substantial interest in immunotherapy and biologicals in IgE‐mediated food allergy. Methods: We searched six databases for randomized controlled trials about immunotherapy alone or with biologicals (to April 2021) or biological monotherapy (to September 2021) in food allergy confirmed by oral food challenge. We pooled the data using random‐effects meta‐analysis. Results: We included 36 trials about immunotherapy with 2126 mainly child participants. Oral immunotherapy increased tolerance whilst on therapy for peanut (RR 9.9, 95% CI 4.5.–21.4, high certainty); cow's milk (RR 5.7, 1.9–16.7, moderate certainty) and hen's egg allergy (RR 8.9, 4.4–18, moderate certainty). The number needed to treat to increase tolerance to a single dose of 300 mg or 1000 mg peanut protein was 2. Oral immunotherapy did not increase adverse reactions (RR 1.1, 1.0–1.2, low certainty) or severe reactions in peanut allergy (RR 1, 6, 0.7–3.5, low certainty), but may increase (mild) adverse reactions in cow's milk (RR 3.9, 2.1–7.5, low certainty) and hen's egg allergy (RR 7.0, 2.4–19.8, moderate certainty). Epicutaneous immunotherapy increased tolerance whilst on therapy for peanut (RR 2.6, 1.8–3.8, moderate certainty). Results were unclear for other allergies and administration routes. There were too few trials of biologicals alone (3) or with immunotherapy (1) to draw conclusions. Conclusions: Oral immunotherapy improves tolerance whilst on therapy and is probably safe in peanut, cow's milk and hen's egg allergy. More research is needed about quality of life, cost and biologicals. Abstract : We systematically reviewed 39 randomized controlled trials about allergen‐specific immunotherapy and/or biologicals in 2244 people with IgE‐mediated food allergy, mostly children. We found that oral immunotherapy is probably safe and effective in peanut, milk and egg allergy. The number needed to treat (NNT) to increase tolerance to a single dose of 300 mg or 1000 mg peanut protein was 2.Abbreviation: NNT, number needed to treat